2007
DOI: 10.1080/15402000701190614
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of One Versus Two Nights of In-Laboratory Continuous Positive Airway Pressure Titration on Continuous Positive Airway Pressure Compliance

Abstract: One versus two nights of CPAP titration did not affect CPAP compliance, but sleep efficiency improved on the second diagnostic night and an extra titration study may be necessary for some patients, especially those with only one diagnostic night.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…A first night effect of CPAP application on sleep architecture has also been described by other researchers (Kaplan et al, 2007; Lorenzo and Barbanoj, 2002); however, it should not have caused the differential effect of PLM indices seen between CPAP groups in our study. The literature also cites evidence of increased PLM arousal indices over continued CPAP use, as the arousal threshold is lowered after an initial sleep rebound and the brain is more susceptible to register EMG activation, further reinforcing the “unmasking” theory (Fry et al, 1989; Kaplan et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A first night effect of CPAP application on sleep architecture has also been described by other researchers (Kaplan et al, 2007; Lorenzo and Barbanoj, 2002); however, it should not have caused the differential effect of PLM indices seen between CPAP groups in our study. The literature also cites evidence of increased PLM arousal indices over continued CPAP use, as the arousal threshold is lowered after an initial sleep rebound and the brain is more susceptible to register EMG activation, further reinforcing the “unmasking” theory (Fry et al, 1989; Kaplan et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…The literature also cites evidence of increased PLM arousal indices over continued CPAP use, as the arousal threshold is lowered after an initial sleep rebound and the brain is more susceptible to register EMG activation, further reinforcing the “unmasking” theory (Fry et al, 1989; Kaplan et al, 2007). …”
Section: Discussionmentioning
confidence: 90%
“…Another very influential finding is that relatively high adherence rates have been reported in some European studies where several nights of hospitalization upon initiation were the norm [82]. However, Kaplan et al did not find this when comparing one versus two titration nights, despite the a priori presumption was that a second night would be beneficial [83]. There may have been a ceiling effect in this study, which demonstrates some of the highest reported compliance rates.…”
Section: Healthcare Facilitymentioning
confidence: 35%
“…Polysomnographic studies are typically conducted in a sleep laboratory which is an unfamiliar environment for patients and is associated with the discomfort of being connected to a recording device with several wires. These environmental changes create a phenomenon known as the “first night effect” [ 7 ], which implicates changes in sleep quality and efficiency resulting in inaccurate and unrepresentative results. Moreover, there are differences in the recording techniques among different sleep laboratories, and until recently a lack of awareness of the implication of rapid eye movement (REM) and nonrapid eye movement (NREM) related apneas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the inconsistency of the results related to different criteria, such as the threshold of oxygen desaturation, exists between different laboratories. Some variability in sleep data may result due to night-to-night variability or the “first night effect” [ 7 ]. Further, in-laboratory PSG requires monitoring by an attending sleep technician.…”
Section: Introductionmentioning
confidence: 99%